Violencia intrafamiliar y su repercusión en el estado emocional de una adolescente de 15 años del cantón Alfredo Baquerizo Moreno, Jujan - Lizarzaburo Vera, Joyce Valeria (2023)
In this case study we studied the influence of domestic violence and its impact on the emotional state of a 15 year old adolescent girl from Canton Alfredo Baquerizo Moreno Jujan, with which through a semi-structured interview we were able to carry out a presumptive diagnosis in which we implemented the use of cognitive-behavioral techniques that helped the patient in her treatment. Also this case study was carried out using the qualitative approach methodology since, in qualitative studies, it is possible to develop questions and hypotheses before, during or after data collection and analysis, which can help to discover the most important research questions and improve them to obtain accurate answers. The present case study is carried out based on interventions that were had with an adolescent patient within the professional practices, in which information was collected through semi-structured interviews, psychological evaluations and application of reagents, all this will help to extract the necessary information to be able to carry out a therapeutic plan based on CBT techniques based on their diagnosis.